Keterbatasan Sarana Dan Prasarana PIAUD Dalam Meningkatkan Mutu Pembelajaran Di Desa Binjai - Agustia, Erine; Yumidar, Yumidar; Sukarti, Mila; Selpiana, Selpiana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study investigates the limitations of facilities and infrastructure in the Early Childhood Islamic Education (PIAUD) program in Binjai Village and explores alternative solutions to enhance the quality of early childhood education. Adequate educational facilities and resources are crucial for supporting effective learning, particularly in developing children’s listening comprehension skills and overall cognitive development. The research employed a case study design with a qualitative approach, complemented by descriptive statistical analysis to strengthen data interpretation. Data were collected through field observations, in-depth interviews with teachers and school principals, and documentation. Thematic analysis was used to identify recurring issues, while frequency counts and percentage distributions were applied to highlight the extent of facility limitations. The findings indicate that physical facilities, including classrooms, learning media, and educational toys, are significantly limited in PIAUD institutions in Binjai Village. These constraints negatively affect the teaching–learning process and hinder the development of children’s potential, particularly in language acquisition and listening comprehension skills. Key contributing factors include inadequate government budget allocation, insufficient teacher training, and low levels of community engagement.To address these challenges, the study proposes several alternative solutions: optimizing local resources, strengthening partnerships with private sectors and donor agencies, and establishing community-based teacher training programs. Implementing these strategies is expected to improve the quality, sustainability, and equity of early childhood education services in Binjai Village